Water robustness of organic thin-film transistors based on pyrazino[2,3-g]quinoxaline-dione conjugated polymer - Ko, Jieun (2022)
A robust air and water stable π-conjugated polymer based on pyrazino[2,3-g]quinoxaline-2,7-dione (PQD) modified with long alkyl side chains on both the donor and acceptor units (PQD-HD-4T-DD) was synthesized and demonstrated to be a novel semiconducting layer for highly air and water stable organic thin-film transistors (OTFTs). Due to the alkyl side chains on the donor and acceptor units, the polymer showed good hydrophobicity preventing water ingression into the crystalline regions of the polymer film. Moreover, the deep highest occupied molecular orbital (HOMO) level and shallow unoccupied molecular orbital (LUMO) level attributed to the contribution of the PQD moiety can prevent air oxidation and nucleophilic attack from water molecules, respectively. We show that the PQD-HD-4T-DD OTFT exhibits excellent electrical stability retaining 78% of its initial charge carrier mobility even after immersing the bottom-gate top-contact OTFT in deionized water for five days without encapsulation.